Emission characteristics of ultrafine particles from bare and Al2O3 coated graphite for high temperature applications - Yadav S.K.; Shukla P.; Joshi M.; Khan A.; Kaushik A.; Jha A.K.; Sapra B.K.; Singh R.S. (My University, 2025)
Owing to its exceptional properties at high temperature, graphite is used in several applications such as structural material and fuel block in high temperature nuclear reactors. Air ingress is one of the serious safety concerns in these reactors. Oxidation of graphite leading to increased porosity affects its mechanical strength and may lead to core collapse resulting in a severe accident. During such a scenario, generation of graphite particles could be the main hazard. Once generated, these particles often in fine and ultrafine sizes, may carry radioactivity to large distances and/or for long times. These particles owing to their higher surface to volume ratio possess an additional inhalation hazard. Ultrafine particles have the potential to enter into respiratory tract and cause damage to body organs. Coating of graphite components is preferred to reduce the oxidation induced damages at high temperatures. In the present work, effect of alumina (Al2O3) coating on the emission characteristics of particles from graphite under high temperature conditions has been investigated. Bare and Al2O3 coated graphite specimens were heated within a closed chamber at varying temperatures during these experiments. Temporal evolution of concentrations of gases (CO and CO2) and particles were measured. The results reveal that Al2O3 coating on the graphite delayed the oxidation behavior and the structure of graphite remained largely intact at high temperatures. A significant reduction in aerosol formation and CO emission was also noticed for the coated specimens. © 2020, The Author(s).